The Role of Digital Marketing in the Development of Tette Chip MSMEs in Lebbek Village - Imroatus Sholehah; Nur Ainiyah; Anas Bagus Mulianto; Royhan Sabilillah; Kamala Ainun Nazilah; M.Tohirul Amin (Regulate: Jurnal Ilmu Pendidikan, Hukum dan Bisnis, 2025)
This study examines the role of digital marketing in the development of the Kripik Tette (Tweet Chips) MSME in Lebbek Village, Pakong District, Pamekasan Regency. Kripik Tette, a traditional Madurese culinary specialty, has significant potential to become a regional flagship product due to its unique manufacturing process, the abundant use of local cassava as the raw material, and its distinctive, authentic flavor. However, the development of this product still faces several obstacles, including limited market access, MSMEs' limited understanding of digital marketing strategies, and the use of simple packaging. This research used a qualitative approach with a case study method through interviews, observations, and documentation of MSMEs. The results indicate that the implementation of digital marketing, particularly through social media, can increase product appeal, expand market reach, and strengthen the branding of the Nira Tweet Chips. Simple training provided to MSMEs has been shown to improve skills in creating promotional content, product packaging, and interacting with consumers. Although still facing obstacles such as limited internet access and a lack of utilization of digital marketing features, this mentoring effort has had a positive impact on increasing the capacity of entrepreneurs. Thus, digital marketing plays a crucial role in encouraging the development of tette chips MSMEs, both economically and as an effort to preserve local culture.